An Analysis of Speaking Barriers in English Learning at Senior High School in Songgon Sub-district - Elgau Krima; Sutami Dwi Lestari; Abdul Halim (LUNAR, 2021)
Speaking is an important things in interaction, and speaking English is very important to learn to communication when people from the different nations meet. This research aimed to find the type and the dominant barriers in speaking English learning at Senior High School in Songgon Sub-district. The research design was descriptive qualitative. The respondent were 160 from three school in Songgon Sub-district, they are 69 respondent from MA Alfatah, 17 respondent from SMA 4 Muhammadiyah, and 74 respondent from SMK Nurut Taqwa which determined by using cluster sampling. The data were taken by using online system of questionnaire and interview. The data from questionnaire was analyzed by using Likert scale. The data analysis was determined based on theory linguistics barrier and non-linguistic barriers. Analysis questionnaire and interview data showed that students at Senior high school In Songgon sub-district have high Barriers in speaking English learning. The type of barriers had by students showed the percentage score of each indicator are 66% in speaking barrier, 57% in lack of vocabulary, 65% poor in grammar, 64% poor in pronunciation, 71% in lack of motivation, 62% in fear of mistake, 61% in anxiety, 65% in lack of confidence, and 57% in shyness. The most dominant barriers had by students are poor in grammar from linguistic factor and lack of motivation from non-linguistic factor.